2012
DOI: 10.1177/001440291207900103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multi-Tier Academic and Behavior Instruction on Difficult-to-Teach Students

Abstract: This article addresses the effects of 3-tiered comprehensive reading and behavior interventions on K-3 student outcomes in 7 urban elementary schools with a high prevalence of students considered difficult to teach. Specific features of each level of the implementation are described including screening and tier placement procedures, scheduling and personnel supports, procedures for ensuring strong implementation with fidelity, procedures for student progress monitoring, and guidelines for instructional decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Overall, 32 studies using an RCT or QED were identified that evaluated the effect of SWPBIS on school‐level outcomes. Six of the studies used an RCT design (Algozzine et al, ; Bradshaw et al, , ; Horner, Sugai, Smolkowski, et al, ; Sørlie & Ogden, ; Waasdorp, Bradshaw & Leaf, ), while 26 studies used a QED design with a comparison group that did not receive SWPBIS training. Characteristics of the collected studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 32 studies using an RCT or QED were identified that evaluated the effect of SWPBIS on school‐level outcomes. Six of the studies used an RCT design (Algozzine et al, ; Bradshaw et al, , ; Horner, Sugai, Smolkowski, et al, ; Sørlie & Ogden, ; Waasdorp, Bradshaw & Leaf, ), while 26 studies used a QED design with a comparison group that did not receive SWPBIS training. Characteristics of the collected studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…A great effort was made to identify all potential studies by using several search procedures, including forward and backward searches and hand searches. Second, Algozzine et al () included both academic and behavioral interventions in their model, therefore, the academic intervention may have also affected students’ academic achievement. Third, there were studies that used the same samples, but different outcomes (Bradshaw et al, ; Waasdorp et al, ), which may increase bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Algozzine et al. () echoed this sentiment, stressing that a focus on behavior is a crucial component of academic efforts, and that a decision to consider academics alone at the expense of behavior may be misguided. The influence of this work on behavior screening research is evident in recent studies regarding the extent to which screening tools predict academic outcomes.…”
Section: The Influence Of Behavioral Functioning On Academic Performancementioning
confidence: 99%
“…Collectively, this research has established the importance of educators considering student behavior, even when their stated purpose is to bolster academic outcomes (Horner et al, 2009;Putnam, Horner, & Algozzine, 2006). Algozzine et al (2012) echoed this sentiment, stressing that a focus on behavior is a crucial component of academic efforts, and that a decision to consider academics alone at the expense of behavior may be misguided. The influence of this work on behavior screening research is evident in recent studies regarding the extent to which screening tools predict academic outcomes.…”
Section: The Capacity Of Behavior Screeners To Predict Academic Perfomentioning
confidence: 99%